Understanding and teaching American slavery - Jay, Bethany; Lyerly, Cynthia Lynn, 1960- (Madison, Wisconsin : The University of Wisconsin Press, 2016)
Perhaps no topic in U.S. history is as emotionally fraught as the nation's centuries-long entanglement with slavery. How can teachers get students to understand the racist underpinnings of that institution--and to acknowledge its legacies in contemporary America? How can they overcome students' shame, anger, guilt, or denial? How can they incorporate into the classroom important primary sources that may contain obsolete and racist terms, images, and ideas? This book, designed for college and high school teachers, is a critical resource for understanding and teaching this challenging topic in all its complexity. Opening with Ira Berlin's reflections on ten elements that are essential to include in any course on this topic, Understanding and Teaching American Slavery offers practical advice for teaching specific content, utilizing sources, and getting students to think critically. Contributors address, among other topics, slavery and the nation's founders, the diverse experiences of the enslaved, slavery's role in the Civil War, and the relationship between slavery and the northern economy. Other chapters offer ideas for teaching through slave narratives, runaway ads, spirituals, films, and material culture. Taken together, the essays in the volume help instructors tackle problems, discover opportunities, and guide students in grappling with the ugliest truths of America's past--Publisher description.
Foreword: The short course for bringing slavery into the classroom in ten not-so-easy pieces / Ira Berlin -- Introduction / Bethany Jay and Cynthia Lynn Lyerly -- Part 1. Slavery and the Classroom. Methods for teaching slavery to high school students and college undergraduates in the United States / James W. Loewen ; Dealing with things as they are : creating a classroom environment for teaching slavery and its lingering impact / Steven Thurston Oliver -- Part 2. Teaching Specific Content. Teaching the origins of slavery in the Americas / Eric Kimball ; Slavery in the new nation : human bondage in the land of liberty / Paul Finkelman ; Blood stained mirrors : decoding the American slave-trading past / Sowande' Mustakeem ; Slavery and the northern economy / Christy Clark-Pujara ; Northern slavery and its legacies : still a new (and unwelcome?) story / Joanne Pope Melish ; Slave resistance / Kenneth S. Greenberg ; Slave culture / Bernard E. Powers Jr. ; The diverse experiences of the enslaved / Deirdre Cooper Owens ; Slavery and the Civil War / Bethany Jay ; Comparative slavery / Laird W. Bergad ; The challenge of slavery since emancipation : from 1865 to the twenty-first century / James Brewer Stewart -- Part 3. Sources and Strategies for Teaching Slavery. Using the WPA slave narratives in the classroom / Cynthia Lynn Lyerly ; Teaching the history of slavery through film / Ron Briley ; Art and slavery / Ray Williams ; In the footsteps of others : understanding slavery through process drama / Lindsay Anne Randall ; "A likely negro" : using runaway-slave advertisements to teach slavery / Antonio T. Bly ; Teaching the history of slavery and its legacy through historical archaeology : Project Archaeology / Sarah E. Miller, James M. Davidson, and Emily Palmer.
Includes bibliographical references and index.
Keywords: Slavery -- History -- Study and teaching -- United States; African Americans -- History -- 19th century -- Study and teaching; African Americans -- History -- 20th century -- Study and teaching; African Americans -- Politics and government -- Study and teaching; African Americans -- Civil rights -- History -- Study and teaching